2020
DOI: 10.1371/journal.pone.0239515
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of breastfeeding practices in Myanmar: Results from the latest nationally representative survey

Abstract: Optimal breastfeeding practices can ensure healthy growth and development of infants, which in the long term can impact the country's economic development. Nevertheless, Myanmar has yet to achieve the WHO's target of 70% for early initiation of breastfeeding, and the country's target of 90% for exclusive breastfeeding. The purpose of this study was to assess the associations between early initiation of breastfeeding and exclusive breastfeeding and bio-demographic, socioeconomic and behavioral factors in Myanma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In line with previous studies, infants perceived as small were less likely to receive EIBF [ 12 , 15 , 19 ]. Small birth size as perceived by the mothers may indicate that the infants had low birth weight, which was a risk factor of EIBF [ 20 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with previous studies, infants perceived as small were less likely to receive EIBF [ 12 , 15 , 19 ]. Small birth size as perceived by the mothers may indicate that the infants had low birth weight, which was a risk factor of EIBF [ 20 ].…”
Section: Discussionsupporting
confidence: 90%
“…The present analysis showed that older children had lower odds of EBF and CBF-2. A large body of evidence has also confirmed that younger children are more likely to be exclusively breastfed than older ones [ 12 , 14 , 15 ]. A possible explanation is mothers’ perception that giving only breastmilk is insufficient as infants grow larger [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, numerous studies from LMICs have shown that health service factors (including breastfeeding counselling in health facilities, ANC visits, and health facility birthing and normal vaginal births) are strongly associated with appropriate IYCF [ 91 , 92 , 93 , 94 ]. Consistent with past studies, the review showed that health service factors were associated with appropriate IYCF in India.…”
Section: Discussionmentioning
confidence: 99%
“…However, the duration of exclusive breastfeeding may differ for migrant mothers depending on parenting duration after delivery, and beliefs and cultural differences. According to the survey in Myanmar, the exclusive breastfeeding rate of Myanmar women was 52.3% (Yadanar et al, 2020). Burmese mothers with healthy infants tend to breastfeed them and give the infants water and rice before 6 months of age to keep them full, hydrated, and prevent colic (Hashmi et al, 2019;Thet et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%